THE MIDIAN STAGE OF THE PERMIAN AND ITS BOUNDARIES - Leven E.Ya. (My University, 1996)
The Midian Stage is suggested to correspond to the Yabeina-Lepidolina Genozone, i.e., to the entire existence time of the index genera. The first occurrence level of Yabeina forms is in the Neoschwagerina margaritae Zone in its stratotype section, and this zone should be considered as a constituent unit of the stage. This is also evident from a significant renewal of fusulinid and smaller foraminifer assemblages at the base of indicated zone, which was caused by a widespread transgression. The Lepidolina kumaensis Zone should be included into the Midian Stage as well. At present, none of the fauna groups seem to be suitable to precisely determine the stage boundaries. This problem remains to be solved in the future.
Keywords: Permian; Paleozoic::Permian; Палеозой::Пермская